Association between Maternal Dietary Diversity and Low Birth Weight in Central India: A Case-Control Study. (30th May 2021) - Sharma, Shantanu; Maheshwari, Sonali; Mehra, Sunil
Abstract : Low birth weight (LBW) is one of the major public health challenges in India. LBW etiology is multifactorial and linked to multiple determinants, including maternal undernutrition and sociodemographic characteristics. The objective of the present endeavor was to assess how maternal dietary diversity and other sociodemographic factors among marginalized populations are associated with the incidence of LBW. The study was a part of the community-based intervention that aimed to improve maternal and child health in the Morena district of Madhya Pradesh, a state in central India. In this case-control study, cases were defined as mothers with an LBW child (<2500 grams) and controls as mothers without an LBW child. A quantitative survey was done with women of reproductive age, having at least one child aged 0–24 months. We calculated the dietary diversity based on the number of food groups consumed during pregnancy by women on a daily basis. Stepwise logistic regression models were built to test for associations between sociodemographic and dietary diversity variables and LBW incidence. There were 157 mothers with and 214 without an LBW child. Women's diets mainly consisted of grains, such as wheat, rice, maize, and roots and tubers. Eggs and meat were consumed by less than 1% of the women. There were 20% lesser chances of an LBW child with increasing maternal dietary diversity scores (odds ratio: 0.79; 95% CI: 0.65, 0.96). The poor maternal diet quality during pregnancy may result in adverse birth outcomes with long-term consequences in a child.